Improving Early Reading Skills Using Illustrated Syllable Cardsamong First-Grade Students - I Made Yudis Saputra; Ardhy Supraba; Paldy (EDUJAVARE: International Journal of Educational Research, 2026)
Initial reading skills are basic skills that must be mastered by elementary school students because they are the foundation for acquiring knowledge at the next level of learning. The results of initial observations in grade I of SDN 110 Saele, East Luwu Regency show that students' initial reading ability is still low, characterized by difficulty recognizing letters, pronouncing syllables, and stringing syllables into simple words. This research aims to improve students' initial reading ability through the use of illustrated syllable card media. The research uses the Classroom Action Research (PTK) method with the Kemmis and McTaggart models which is carried out in two cycles, each including the stages of planning, implementation of actions, observation, and reflection. The research subjects were 18 students in grade I of SDN 110 Saele. The data collection technique was carried out through observation and initial reading tests, while the data was analyzed descriptively quantitatively. The results of the study show that the use of illustrated syllable card media is able to improve students' initial reading ability as shown by increasing student activity during learning, better learning implementation, and increasing the completeness of learning outcomes to achieve the set success indicators. Thus, the medium of illustrated syllable cards is effectively used as an alternative learning medium to improve the initial reading ability of elementary school grade I students.